The Use of Malaysian Natural Coral and Calcium Phosphate Cement as Bone Graft Substitute In Reconstructive Bone Surgery of Sheep - Ahmad, Fadilah (2005)
Bone defects, which often occur as a result of various diseases have been r ~ o r twsith~ au~togr aft or &ogr&. However, their we is always associated with limited supply and to overcome this, biomaterials are considered as an alternative. Synthetic biomaterid such as calcium phosphate cement (CPC) available in the mark& has been used in bone defect. Another possie sotvce is mttud ~~ such as rtstttud cmd. Therefore, the present study was designed to evaluate the natural coral and compare it to the c~~nrnercidlayv daMe CP€ post-implantation in sheep femoral bone. Twenty one adult male sheep, weighing between 15 - 20 kg were used in this study. The &mak were divided into two groups: 9 & A s in group 1 (CK) anb 12 minds in group 2 (cod).Coral blocks (Porites spp.) were prepared and processed according to the protocol established by the Tissue Bank of the Malaysian Institute for Nuclear Technology Research (MINT). Commercially available CPC implant (Rebone Gutai, Shanghai Rebone Biomaterials Co., Ltd, China) was used as comparison. A bone defect (2.5 cm x 0.5 cm x 0.5 cm) was created surgically on the proximal part of femur before it was replaced by the implants. Radiographs were obtained immediately after the surgery and at 2,4,8 and 12 weeks post-implantation. Ultrasonographic examinations were carried out at 1, 2, 4, 8 and 12 weeks post-implantation using ultrasound machine (TOSHIBA Capasee 11) connected with 7 MHz frequency transducer. Weekly blood samples were collected from all animals via jugular vein for calcium and phosphate analyses. The sheep were sacrificed at 2,4,8, and 12 weeks post-implantation and the implant sites were examined grossly. Samples of the implant site were taken for histological examination. Radiograph taken at 2 weeks post-implantation revealed mild lost of coral implant architecture and occasional development of radiolucent zone. At 4 weeks post-implantation, coral implant margins became indistinctive, prominent radiolucency zone and the intrinsic architecture was difficult to appreciate. The central part remained more radio opaque, indicating that resorption was proceeding centripetally. At 8 weeks and 12 weeks postimplantation, the coral implant was completely resorbed. In contrast, there was no change in CPC implant at weeks 2 4 and 8 post-implantation At 12 weeks post-implantation, a slight fuzzy appearance had developed at the margins of CPC implant indicating slower progress of resorption. However, the CPC implant remained visible on the radiograph throughout the study period. Ultrasonographic examination for up to 4 weeks post-implantation revealed that the coral implant was still visible at the implant site. However, by 8 wdwpost-inpfmta~the~~wasfullyr;escrrbedandsofttissues were observed at the implant site. Meanwhile, for the CFC implant, the ulPr%sonographic examination demomimted that the implant was still dearly visible for up to 12 weeks post-implantation. . - .-. - - - -- . -- The serum calcium levels found in both animals implanted with coral and CPC during the study period revealed no significant different, except for weeks land 10 in coral group where the level was significantly increased. While for the serum phosphate level there were significant increased at weeks 1 and 3 for CPC group and at week 11 for coral group. However, by w e e k l 4 , ~ ~ c a i c i m r t d ~ - f e v e E s w e r e ~ o o ~ a measured before implantation These indicated that the coral and CPC implant were biodegradable.Microscopically, the natural coral implanted into bone tissue showed rapid resorption and progressive replacement by new bone. At 12 weeks postimplantation, the implant site was almost completely closed and surrounded by new bone. Meanwhile, the CPC implant demonstrated a marginal bone formation at the end of the 12 weeks study. Scanning electron microscopy observation of the coral implant at 2 weeks postimplantation showed that the implant was irregularly eroded on the surface, but the morphology of the pores was conserved. At 4 weeks, coral implant deteriorated and the shape of the pores changed, indicating increased coral degradation. At 8 and 12 weeks, no more coral was detected and the implant site was filled with dense collagenous extracellular matrix. Meanwhile, the CPC implant was characterized by deformity and broken surface of the implant. Some areas revealed granular appearance due to attachment of the cells. In conclusion, results of the present study showed that natural coral implant was rapidly resorbed and was almost completely filled by new bone formation at the end of the study. In contrast, the CPC implant has a very slow resorption rate and remained clearly visible by week 12 postimplantation. Thus, the coral implant could be a possible and good candidate for bone graft.